CONSTITUTION AND DEMOCRACY: The Relationship between Law and Popular Sovereignty - Yunus, Nur Rohim (BULETIN ADALAH, 2023)
This essay discusses the close relationship between the constitution, democracy, and law in realising a sovereign state based on the rule of law. This essay highlights the role of the constitution as the primary foundation that regulates the division of power, individual rights, and governance mechanisms in a democratic system. In this context, popular sovereignty is a fundamental principle that requires the people to actively form and supervise legal policies. This essay explains that the law must reflect the people's will, guarantee justice, and ensure social welfare through a transparent and accountable process. In addition, enforcing the law based on the people's sovereignty requires a fair and participatory system, which allows every individual to participate in legal decision-making. This essay concludes by emphasising that a healthy relationship between the constitution, democracy, and law is the key to creating a just and sovereign state, where the law serves social justice for all people.